Slums effect on urban sustainability: Suggested planning mechanisms for development - Jasim, Ihsan Abbas; Al-Tamimi, Ahmed Hani; Al-Maliki, Laheab A.; Al-Mamoori, Sohaib K. (Quaestiones Geographicae, 2024)
Slums are considered one of the largest problems that threaten our urban environment, and their negative impact is exacerbated by the passage of time without a radical solution. This research investigated measures that are successful in achieving sustainable urban development within slums or surrounding urban areas. Reducing the negative aspects accompanying the traditional remedies for this phenomenon, which Iraq is currently suffering from, has become a widespread trend in most Iraqi cities. As a result, there emerged belts surrounding urban areas, causing severe repercussions, some of which can be addressed. However, most problems are challenging to address because they affect the urban structure. In Iraqi cities, slums are a feature of the city’s transformation phase, distorting their essence. This phenomenon directly and indirectly affects sustainable urban development by conflicting with one of the most important pillars of sustainable development: not to pass on problems to future generations. Over the past decade, our cities have been formed with slums being a large part of their structure. This poses significant challenges for future generations, which will be difficult to solve unless we proactively address them with effective solutions to mitigate their impact. After reviewing various remedies for this problem, it was found that the proposed treatments were unsuitable for the Iraqi situation. The research proposes the idea of exchange (land versus time). When comparing this strategy with the rest of the treatments, it has been found to be the best solution for slums in Iraq, meeting the requirements of sustainable urban development.